Are we just in providing Health for all? - Maridal, Hans Kristian; Bhatta, Netra Prasad; Rajbanshi, Sushma (Health for All, 2013)
Replacement of original paper 27/09/2013. After the publication of the paper, the authors themselves reported unacceptable level of irregularities in the paper. The authors successfully provided justification, and helped the editors to prepare the revised paper. Health for All Vol.1(1) 2013: 3-6